Tenosynovial giant cell tumours of the foot and ankle: a retrospective single centre experience with surgical treatment of 34 cases - Christian Scheele; Norbert Harrasser; Simone Beischl; Dietmar Dammerer; Ulrich Lenze; Carolin Knebel; Rüdiger von Eisenhart-Rothe; Florian Lenze (BMC Cancer)
Abstract Background Tenosynovial giant cell tumour (TGCT) is one of the most prevalent soft tissue tumours of the foot and ankle. Although typically benign, it can exhibit locally aggressive behaviour. This study aims to evaluate the distribution, surgical management, and recurrence rates of localized (L-TGCT) and diffuse (D-TGCT) forms of TGCT. Methods A retrospective study of 34 TGCT cases in the foot and ankle treated surgically between 2010 and 2023 was conducted. Inclusion criteria required a histologically confirmed diagnosis and a minimum potential follow-up period of 18 months. Patient demographics, radiological findings, surgical approach and recurrence rates were evaluated. Results Of 34 cases, 61.8% were L-TGCT and 38.2% were D-TGCT. L-TGCT had a significantly shorter duration of symptoms (median: 6 months) than D-TGCT (36 months, p = 0.01) and affected significantly more females (76.2%; p = 0.013). Nineteen cases were intraarticular, and 15 cases extraarticular manifestationsMacroscopically complete resection was achieved in 95.2% of L-TGCT cases and 69.2% of D-TGCT cases (p = 0.037). The recurrence rate with limited follow-up was 26.7% for L-TGCT and 50.0% for D-TGCT (p = 0.263). Time to recurrence was 7.0 months for L-TGCT and 12.0 months for D-TGCT (p = 0.287). In 40% of these cases, therapeutic intervention was performed. Conclusion In the foot and ankle, L-TGCT is more common in females, presents earlier after symptom onset, and has a higher rate of complete resection, whereas D-TGCT has a longer symptom duration and higher recurrence rates. It’s important for orthopaedic surgeons to weigh surgical margins against functional results, as stable outcomes appear to be attainable even in cases of residual or recurrent tumours.